The Impact of Corporate Social Responsibility on Consumer Attitude with The Mediating Effect of Brand Loyalty, Brand Skepticism, and Brand Authenticity - Dadhich , Vaibhav; Gupta , Dr Srikant; Ivaturi , Sravanti; Sharma , Prachi (International Journal of Accounting and Economics Studies, 2025)
The study explores the influence of Corporate Social Responsibility (CSR) on consumer behavior, emphasizing the mediating roles of brand skepticism, brand loyalty, and brand authenticity. In an increasingly consumer-driven market, CSR initiatives have gained prominence in shaping perceptions and behaviors. Despite existing studies highlighting CSR's benefits, gaps remain in understanding its interplay with mediating constructs. This study addresses these gaps through a quantitative design, collecting data from 100 respondents in the Delhi NCR region. Statistical analyses, including structural equation modeling (SEM), reveal a significant positive relationship between CSR initiatives and consumer behavior. The findings indicate that transparent CSR practices reduce brand skepticism, while fostering loyalty and enhancing authenticity, which collectively mediate the impact on consumer behavior. The study contributes both theoretically and practically, providing a comprehensive framework for integrating CSR into branding strategies. Businesses are advised to adopt authentic, transparent CSR approaches to align with consumer expectations, thereby enhancing trust and loyalty. The findings highlight the nuanced role of mediators, suggesting that CSR's effectiveness is maximized through tailored initiatives. Future research should incorporate cross-cultural and longitudinal studies to validate and expand on these insights, ensuring a deeper understanding of CSR's implications across diverse industries.
Keywords: Brand Authenticity, Brand Loyalty, Brand Skepticism, Consumer Behavior, Corporate Social Responsibility (CSR), Sustainable Branding